Discoloration of Stretched Clear Elastomeric Chains by Dietary Media (An in vitro study) - Abass , Athraa A; Alhuwaizi , Akram F (Journal of Baghdad College of Dentistry, 2017)
Background: With the increasing demand on esthetic orthodontic appliances, discoloration of clear elastomeric chains and modules remains an issue which concerns both orthodontics and patients. This in vitro study was conducted to evaluate the effect of exposing stretched clear elastomeric chains from six different companies (Ortho Technology, Ormco, Ortho Organizer, American Orthodontics, Opal and G&H companies) to three types of dietary media (tea, coffee and turmeric).Materials and methods: A total of 960 lengths of six modules were cut from short type elastomeric chain; 160 pieces from each brand. The specimens were stretched 50%, placed on plastic boards, and incubated in water at 37Â°C for 1 day, 7 days, 14 days and 28 days. Once a day, the specimens were immersed for ten minutes in the testing dietary media, washed and then returned back to the water container. Color measurements were made before and after incubation of the specimens. Digital image were taken by an SLR digital camera and the color changes were calculated according to CIE L*a*b* color space system by Adobe Photoshop program. The resulting data were statistically analyzed using ANOVA and LSD tests.Result: Elastomeric chains from AO, Opal and G&H companies were the most brands prone to discoloration. Ortho Organizers and Ortho Technology chains were the least prone to discoloration. Tea, coffee and turmeric solutions discolored elastomeric chains from all companies in a variable degree, however turmeric caused significantly more discoloration, followed by tea and least by coffee. The amount of discoloration caused by tea and coffee increases gradually to peak at 28 days, while most of the discoloration caused by turmeric was in the first day and reached a plateau in a week.Conclusion: To decrease the discoloration of clear elastomeric chains the consumption of colored dietary media especially spices like turmeric are to be discouraged.